Promoting adult learning - Miyamoto, Koji, 1949- (Organisation for Economic Co-operation and Development, 2005)
This publication provides policy guidance in an area that has been given little policy priority until recent years. It brings together key lessons from 17 OECD countries, providing evidence on the strategies in place to improve adults participation in learning. It addresses potential barriers to learning as well as the policies to remedy them. Among these are policies for increasing and promoting the benefits of adult learning to make them transparent and easily recognized. Other policy levers include economic incentives and co-financing mechanisms that can raise the efficiency of adult learning provision, while delivering quality learning that is adapted to adults needs. Finally, policy making can be improved via coordination and coherence in a field that is characterized by a wide variety of stakeholders, including ministries of education and ministries of labor.--Publisher description.